THE URGENCY OF ENHANCING ECOLOGICAL LEGAL CULTURE IN ENVIRONMENTAL PROTECTION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Environmental protection has become a global priority as climate change, resource depletion, and biodiversity loss increasingly threaten human well-being and sustainable development. Strengthening ecological legal culture is a vital factor in addressing these challenges, as it ensures that citizens, institutions, and government bodies recognize, respect, and adhere to environmental laws. An advanced ecological legal culture fosters responsible behavior toward the environment, increases public participation in environmental decision-making, and promotes the effective implementation of legal and policy frameworks. In the context of rapid industrialization, urbanization, and socio-economic reforms, enhancing ecological legal knowledge and awareness among the population is particularly urgent. This includes improving environmental education, strengthening legal enforcement mechanisms, and increasing accountability for ecological violations. The abstract highlights the significance of ecological legal culture as a foundation for sustainable environmental governance and underscores the importance of developing lawful, eco-conscious attitudes in society.